Escape behavior in gravid and non-gravid females of Gonatodes albogularis (Squamata: Sphaerodactylidae) - Domínguez López, Moisés Elias (2018)
Theoretical models of predator-prey relationships describe tradeoffs between energetic and other costs of escape, effectiveness of escape behavior, and predation risk. These models predict that an animal will flee when the expected fitness cost due to risk of predation becomes equal to the the cost of the escape or post-encounter fitness is maximized, depending on the model. In this framework, several individual and ecological variables have been shown to affect escape patterns, but the effect of reproductive status has been studied in few species. We assess differences in escape behavior between gravid and non-gravid females of Gonatodes albogularis. Lizards were surveyed by applying a free search method along independent transects. For each lizard, we determined reproductive status as gravid or non-gravid and recorded several variables related to escape behavior. We made a discriminant function analysis to see whether the state of individuals affect escape behavior. Our results show that the escape variables distance fled, the final distance and the distance to refuge differ between gravid and non-gravid females. These findings support predictions based on risk and cost, but do not support models of flight initiation distance. Such differences could be related to a physiological process known as behavioral compensation, through which some individuals (gravid females in our case) modify their behavior to offset predation risk. Further studies are needed to see if behavioral compensation can be explained in terms of adaptive processes in G. albogularis.